Three Phase Load Flow Algorithm Based On Positive Sequence for Unbalanced Power Systems - Sugiarto, Sugiarto; Hadi, Sasongko Pramono; Tumiran, Tumiran (2011)
one of the problems encountered in power system is the appearance of unbalanced voltages and currents in the presence of long un-transposed transmission lines or inconsistanced loading formed by users. To asses these unbalances effects in any detail, a 3-phase-load-flow solution that allows to represent of all possible unbalances as they occur in three phase load flow in the phase frame of reference which based on the sequence program developed for the specific purpose of solving the 3-phase-load-flow problem such as the inductive and resistive effects of multiconductor transmission lines and transmission line losses. To show an assessment of the proposed three phase load flow into unbalance problem, 5-bus transmission networks without transpositions were tested. Moreover, the results revela that solving the load flow problems with newton-Raphson can considerably work by simulation program when comparing with some scenarios of unbalance load of the test network